Substitutions in the hydrophobic core of the alpha-factor receptor of Saccharomyces cerevisiae permit response to Saccharomyces kluyveri alpha-factor and to antagonist. - Marsh, L (1992)
Mutations in the Saccharomyces cerevisiae alpha-factor receptor that lead to improved response to Saccharomyces kluyveri alpha-factor were identified and sequenced. Mutants were isolated from cells bearing randomly mutagenized receptor gene (STE2) plasmids by an in vivo screen. Five mutations lead to substitutions in hydrophobic segments in the core of the receptor (M54I, S145L, S145L-S219L, A229V, L255S-S288P). Remarkably, strains expressing these mutant receptors exhibited positive pheromone responses to desTrp1,Ala3-alpha-factor, an analog that normally blocks these responses. The M54I mutation appeared to affect only ligand specificity. The other mutations conferred additional effects on signaling or recovery. Two mutants were more sensitive to alpha-factor than wild type (S145L, A229V). One mutant was more sensitive to alpha-factor-induced cell cycle arrest initially, but then recovered more efficiently (S145L-S219L). One mutant (L255S-S288P) conferred positive pheromone responses to alpha-factor as assayed by FUS1-lacZ reporter induction, but did not display growth arrest. The hydrophobic receptor core thus appears to control activation by some ligands and to play roles in aspects of signal transduction and recovery.